Appointment scheduling and cost in first opinion small animal practice. Issue 10 (October 2019) - Corah, Louise; Lambert, Alison; Cobb, Kate; Mossop, Liz
Abstract: Approximately half of first opinion, small animal consultations exceed their allocated time and there's a growing call in the UK for longer consults. The aim of this study was to investigate and describe allocated appointment length in first opinion, small animal practice in the UK. Almost half (49.8%) of consults were scheduled for 15 min, with a further 39.4% scheduled for 10 min. Nearly all participants (97.1%) reported flexibility when booking appointments, scheduling longer appointments for conditions predicted to require more time. However, the majority (68.1%) reported no additional cost charged to the client for a longer consult. Furthermore, 54.7% of the survey respondents offered nurse appointments free of charge. A restructured approach to consult scheduling for both Veterinary Surgeon and Registered Veterinary Nurse (RVN) consultations could help to improve workforce wellbeing, utilise the vast knowledge and skill sets of RVNs and improve financial metrics. Abstract : Appointment length; Clinical practice; Consultation; Practice management; Veterinary profession; Veterinary medicine; Business